Enhancing Antioxidant Benefits of Kombucha Through Optimized Glucuronic Acid by Selected Symbiotic Fermentation Culture - Yu-Chieh Chou; Hui-Wen Lin; Chung-Yi Wang; Chen-Che Hsieh; Shella Permatasari Santoso; Shin-Ping Lin; Kuan-Chen Cheng (MDPI AG, 2024)
Kombucha, a functional beverage rich in glucuronic acid, is fermented in the presence of acetic acid bacteria and yeast as the primary microorganisms. Glucuronic acid is recognized for its various physiological benefits, such as detoxification, antioxidation, and anti-inflammation. To optimize the glucuronic acid content in kombucha, various strain combinations by selecting fermented sources were accomplished. According to the experimental results, kombucha produced through co-fermentation with Pichia anomala and Komagataeibacter hansenii, with glucose-added black tea as the carbon source, exhibited the highest glucuronic acid production. A response surface methodology found that under optimized conditions of a 12.27% (w/v) carbon source concentration, a 10.07% (w/v) substrate concentration, and a 28.4 °C temperature, the highest glucuronic acid production reached 80.16 g/L, which represented a 2.39-fold increase compared to the original kombucha. Furthermore, the total polyphenol content increased by 3.87-fold, while DPPH and ABTS free radical-scavenging capacities increased by 1.86- and 2.22-fold, respectively. To sum up, these observations reveal the potential for commercial production of glucuronic acid-enriched kombucha and contribute to the development of functional food products related to kombucha in the future.